Impatiens cyclosepala Hook. f. ex W.W. Sm. – a new species record for the flora of India from Arunachal Pradesh - Tiwari, Umeshkumar L.; Chowlu, Krishna; Borah, Souravjyoti (Biodiversity: Research and Conservation, 2018)
The paper reports Impatiens cyclosepala Hook. f. ex W.W. Sm. as a new addition for India from Arunachal Pradesh. The species was, till to-date, known only from more than a 100 years old collection from NW Yunnan.